Earth - Van Rose, Susanna; Streeter, Clive (New York : Dorling Kindersley, 2000)
Explores the secrets of the Earth, answering such questions as what is at the center of the Earth? Why is seawater salty? How was our atmosphere created? What does the ocean floor look like?
Includes index.
Wilson's Children.
6.3.
6.3
5-8
Keywords: Earth sciences -- Juvenile literature; Earth sciences; Earth sciences